2010
DOI: 10.1007/s12562-010-0312-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth, nutrient utilization, oxidative condition, and element composition of juvenile red sea bream Pagrus major fed with fermented soybean meal and scallop by-product blend as fishmeal replacement

Abstract: A feeding trial was conducted to evaluate the effect of fermented soybean meal and scallop by-product blend (3:2) (FP) on the performance of juvenile red sea bream. Five isocaloric diets were prepared by replacing 0% (FP0), 15% (FP15), 30% (FP30), 45% (FP45), and 60% (FP60) fishmeal (FM) protein with FP, respectively. Triplicate groups of fish (initial mean weight 2.83 g) were fed the test diets for 45 days in a flowthrough seawater system. The results demonstrated that growth rates of fish fed FP0, FP15, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 33 publications
(56 reference statements)
4
9
0
Order By: Relevance
“…In this experiment, palatability was not adversely affected by type of SBM (regular SBM or MSBM) inclusion in the diet; however, the level of SBM inclusion adversely affected the feed intake. In general, feed intake has an inverse relationship to higher replacement of FM with plant proteins in omnivorous and carnivorous fish feed (Kader & Koshio, 2012;Kader et al, 2011). There was a decreasing trend in feed intake with increasing dietary SBM and MSBM level, similar to the findings of some previous studies ingredients to increase voluntary feed intake.…”
Section: Feed Intake Growth and Nutrient Utilizationsupporting
confidence: 84%
“…In this experiment, palatability was not adversely affected by type of SBM (regular SBM or MSBM) inclusion in the diet; however, the level of SBM inclusion adversely affected the feed intake. In general, feed intake has an inverse relationship to higher replacement of FM with plant proteins in omnivorous and carnivorous fish feed (Kader & Koshio, 2012;Kader et al, 2011). There was a decreasing trend in feed intake with increasing dietary SBM and MSBM level, similar to the findings of some previous studies ingredients to increase voluntary feed intake.…”
Section: Feed Intake Growth and Nutrient Utilizationsupporting
confidence: 84%
“…The results of FM replacements by Bacillus spp. FSM in rainbow trout, Oncorhynchus mykiss [25], and red sea bream, Pagrus major [30], and utilization of A. oryzea FSM and A. oryzea directly mixed feed in parrotfish, Oplegnathus fasciatus [26] and olive flounder, Paralichthys olivaceus [31], showed higher growth rate and feed utilization than the control, while the survival rates were increased. Therefore, A. niger might have similar potential in SM fermentation, since it can yield functional substances; protease [15][16][17], cellulose and hemicellulases [19], lipase [20], phytase [21] and tannase [22], etc., during the process.…”
Section: Discussionmentioning
confidence: 99%
“…Refstie, Helland, and Storebakken () revealed that soybean meal can be included in diets fed to rainbow trout at levels from 250 to 800 g/kg of their diet. Researchers have shown that it is possible to replace up to 300 g/kg fish meal protein by soybean, malt protein flour and corn gluten meal in the diets of juvenile red sea bream (Abdul Kader et al., ; Deng et al., ; Tusche et al., ). Wu, Rosati, Warner, and Brown () explained the poor performance at higher levels of fish meal replacement by poor nutrients availability.…”
Section: Discussionmentioning
confidence: 99%